Comparative morphometric characteristics of the working surface of endodontic rotary nickel-titanium instruments after maximum cyclic loading - Yu. A. Dombrovskaya; T. O. Paderina; K. A. Benken; E. Yu. Lubskaya; A. V. Silin (Эндодонтия Today, 2022)
Aim. Is the morphometric analysis of the working surfaces of endodontic rotating nickel-titanium instruments.Materials and methods. The chemical composition and physical properties of the three types of endodontic rotating nickel-titanium F2 instruments have been analyzed: proptaper Universal (PTu, Dentsply, Maillefer, Ballaigues, Switzeland), Ultrataper (Eurofile, China) and Superfile (Eurofile, China) protapers. The evaluation of endodontic treatment of 75 endoblocks was also carried out.Results. The research work shows that endodontic rotary instruments have both different chemical composition and heterogeneity of the alloy. The average comparable percentage of titanium and nickel in the studied alloy samples has been revealed. The quality of endodontic treatment of the endoblocks’ channels with various rotating nickel-titanium instruments is also comparable and meets the specified criteria.Conclusion. The morphometric analysis has revealed a difference in the structure of the metal alloy of the F2 protapers, with a comparable content of nickel (46-52%) and titanium (38-41%). The content of pure nickel-titanium alloy along the periphery of the endodontic instrument in Universal protapers ensures high cutting ability of the faces. The obtained data on different resistance to cyclic loads should be taken into account in the endodontic treatment of multi-root teeth. The analysis of the structure of the nickel-titanium alloy indicates the predetermination of the development of the tool’s fracture with prolonged use and the need to take into account the cycles of the endodontic rotary tool.